PERAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MENINGKATKAN KUALITAS PEREMPUAN SUKU ASLI PAPUA DI KOTA SORONG - Hujriman, Hujriman; Takina, Magfirah (Muadalah : Jurnal Hukum, 2022)
Nowadays, the existence of women should not be underestimated because their presence in various fields ranging from political, economical, and social sectors shows that they play an important role in the development of a country. However, many women still experience discrimination and are seen as subordinate to men. It is an obstacle for women to empower themselves. In Sorong, the local culture tends to prioritize men. In the traditional Papuan marriage culture, a man pays a certain nominal when proposing a woman, making him think he has bought the Papuan woman so that he has the right to act arbitrarily and even resort to violence. This study aims to investigate the role of the Office of Women's Empowerment and Child Protection in improving the quality of indigenous Papuan women and the inhibiting and supporting factors in carrying out its role. The research used a descriptive qualitative method with an empirical juridical approach. Data were collected through interviews, observation, and documentation. The findings show that the roles of the Office of Women's Empowerment and Child Protection in improving the quality of Papuan women are divided into two stages: skill training and motivation (through socialization). The inhibiting factors include, first, the budget is often disbursed too late, so it slows down every program that has been designed, and second, societies’ participation. The supporting factors were, first, the government policy, and second, the budget.